Livelihood strategies in the context of population pressure : a case study in the Hararghe Highlands, Eastern Ethiopia - Kirsten, Johann F. (University of Pretoria, 2013)
Thesis (PhD (Rural Development Planning))--University of Pretoria, 2006.